1997
DOI: 10.1590/s0100-879x1997000600006
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the development of renal complications of diabetes mellitus in São Paulo city

Abstract: The incidence of diabetic end-stage renal failure (ESRF) varies worldwide and risk factors have been demonstrated in several populations. The objective of the present study was to identify possible factors associated with the risk of development of ESRF in patients with diabetes mellitus (DM). Two groups of diabetic subjects were included in a case-control study: 1) one group was submitted to renal replacement therapies, attending dialysis centers in São Paulo city and 2) the same number of controls without cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…Furthermore, Ejerblad et al [27] found a slightly increased risk in those who smoked for a longer duration (odds ratio among smokers for >40 years 1.45, 95% confidence interval 1.00–2.09) and in those with a higher cumulative cigarette consumption (odds ratio among smokers for >30 pack years 1.52, 95% confidence interval 1.08–2.14). Higher cumulative doses were associated with an increased risk of developing kidney disease in several other studies [25, 33, 35]. A dose-response relationship was not assessed in most studies.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, Ejerblad et al [27] found a slightly increased risk in those who smoked for a longer duration (odds ratio among smokers for >40 years 1.45, 95% confidence interval 1.00–2.09) and in those with a higher cumulative cigarette consumption (odds ratio among smokers for >30 pack years 1.52, 95% confidence interval 1.08–2.14). Higher cumulative doses were associated with an increased risk of developing kidney disease in several other studies [25, 33, 35]. A dose-response relationship was not assessed in most studies.…”
Section: Resultsmentioning
confidence: 98%
“…The definitions of current smokers varied considerably and in some studies included both those who smoked >100 cigarettes per lifetime and currently smoked [25, 26]; other studies included those who smoked ≥1 cigarette/day for a specified length of time, e.g., 30 days, prior to study enrollment [27,28,29,30], while other studies did not provide a definition [22, 23, 31, 32]. There was also heterogeneity in the baseline renal function assessment and measurement/documentation of CKD outcome; some studies obtained markers of renal injury (proteinuria or serum creatinine or estimated glomerular filtration rate) [8, 9,23,24,25, 27, 28,30,31,32,33,34], and others used diagnosis codes obtained from various reports (i.e., discharge summaries, end-stage renal disease database, or death certificates) [21, 22, 26, 29, 35]. Two studies included in this review excluded diabetics [24, 33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O sexo masculino havia se associado a maior risco de ND em alguns estudos (31,32). Embora tenhamos obtido maior número de homens nos grupos complicados, a falta de representatividade da nossa amostra não permite tal análise.…”
Section: Discussionunclassified
“…Nos homens ocorre maior comprometimento do trato urinário superior associado à proteinúria. E, em mulheres há maior comprometimento do assoalho pélvico (por multiparidade e até mesmo pela disposição anatômica do aparelho urogenital) (15) . A prevalência de sintomas urinários em mulheres de 40 a 60 anos, é de 16,0% de incontinência urinária de esforço, com prevalência maior na faixa etária de 40 a 55 anos (16) .…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified